2011
DOI: 10.1111/j.1540-8159.2010.02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Mortality and Pacing Outcomes of Patients with Permanent Pacemaker Implantation after Cardiac Surgery

Abstract: The majority of patients who require PPM after cardiac surgery are not PPM dependent in the long term. Requiring a PPM after surgery is not associated with long-term mortality after adjustment for patient-related risk factors and cardiac surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 35 publications
11
54
2
3
Order By: Relevance
“…[2][3][4][19][20][21] In contrast to these results, we failed to find any deleterious effect of PPI on mortality or heart failure status in patients undergoing TAVI, even in patients with left ventricular dysfunction at baseline. However, these finding are consistent with prior studies in the cardiac surgery field, 22 as well as with some prior smaller TAVI series. [8][9][10][11] Results from the Dual Chamber and VVI Implantable Defibrillator (DAVID) trial, Mode Selection Trial (MOST), and Multicenter Automatic Defibrillator Implantation Trial II (MADIT-II) showed that the deleterious impact of pacing on heart failure or mortality depends on cumulative percent time of ventricular pacing.…”
Section: Ppi After Tavi and Clinical Outcomessupporting
confidence: 83%
“…[2][3][4][19][20][21] In contrast to these results, we failed to find any deleterious effect of PPI on mortality or heart failure status in patients undergoing TAVI, even in patients with left ventricular dysfunction at baseline. However, these finding are consistent with prior studies in the cardiac surgery field, 22 as well as with some prior smaller TAVI series. [8][9][10][11] Results from the Dual Chamber and VVI Implantable Defibrillator (DAVID) trial, Mode Selection Trial (MOST), and Multicenter Automatic Defibrillator Implantation Trial II (MADIT-II) showed that the deleterious impact of pacing on heart failure or mortality depends on cumulative percent time of ventricular pacing.…”
Section: Ppi After Tavi and Clinical Outcomessupporting
confidence: 83%
“…Survival was assessed using the electronic medical records, social security death index and the VA Beneficiary Identification Records Locator Subsystem 10 11. In patients who died, the cause of death was ascertained from the death certificates.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariable logistic regression included the time unit (day vs. night or weekday vs. weekend), mortality risk estimate and priority of the operation (elective vs. urgent or emergent). The method of adjusting for patients' risk by including the mortality risk estimate in the multivariable model has been validated before [14-16]. Indicator variables were used when examining the mortality rate in relation to the priority surgery and to the months of the year.…”
Section: Methodsmentioning
confidence: 99%